Key Factors for Assessing Small and Rural Municipalities’ Readiness for Smart City Implementation - Nkhangweni Lawrence Mashau; Jan Hendrik Kroeze; Grant Royd Howard (Smart Cities, 2022)
The concept of a ‘smart city’ is now commonly used to describe the use of various digital and other technologies, to collect data to provide information that can be used to manage resources efficiently and provide a better standard of living for the citizens. Small and rural municipalities in developing countries face growing challenges in managing their resources, to provide basic services such as housing, education, transport, health, water and electricity to the citizens. This research is aimed at identifying key factors that could assist small and rural municipalities to assess their readiness for smart city implementation. A systematic literature review methodology was employed to provide an exhaustive summary of substantiated research relevant to the research aim and to synthesize key factors that are crucial to assess small and rural municipalities’ readiness. This study was conducted between January and July 2022. As a contribution, this study identified and synthesized key factors to be addressed when determining a municipality’s readiness to become a smart city. Through the use of ATLAS.ti to analyze the data, the study identifies the following key factors: infrastructure, the environment, skills, innovation, technology, the economy, citizens, culture, finance, the public sector, private organizations, data, management, policies, internet connectivity, education and energy. Advancing these key elements should also help small and rural municipalities, who are not yet ready to actuate a smart city, to prepare for such an endeavor, in order to address service delivery issues, the economy and the quality of life of their citizens.